2015
DOI: 10.1111/jfpp.12433
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Microencapsulated Fish Oil during Refrigerated Storage

Abstract: Microencapsulation of fish oil was done by spray drying. Commercially available milk was used to form microsized emulsion. Ginger essential oil (0.25%) was used as source of antioxidant. Fish gelatin and maltodextrin were tested for their ability to serve as wall materials for microcapsules with milk protein. Encapsulation efficiency was improved significantly (P < 0.05) by the addition of fish gelatin/ maltodextrin as wall material. Flow properties of fish oil encapsulate were passable to poor. Fatty acid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…In our previous report on oxidative stability of fish oil microencapsultes, we have reported the properties and oxidative stability of fish oil encapsulates (Jeyakumari et al 2014;Jeyakumari et al 2015).…”
Section: Properties Of Fish Oil Microencapsulatesmentioning
confidence: 99%
“…In our previous report on oxidative stability of fish oil microencapsultes, we have reported the properties and oxidative stability of fish oil encapsulates (Jeyakumari et al 2014;Jeyakumari et al 2015).…”
Section: Properties Of Fish Oil Microencapsulatesmentioning
confidence: 99%
“…The composition of the emulsion was selected based on our previously reported results. [14,15] Initially, chitosan was dissolved into the 1% aceticacid solution followed by other wall materials such as bovine gelatin and maltodextrin. After the complete dissolution of the wall material, the fish oil-oregano extract blends/fish oil were added to wall material slowly while stirring at 1000 rpm for 10 min using magnetic stirrer.…”
Section: Preparation Of Emulsion and Spray Dryingmentioning
confidence: 99%
“…[30] Microencapsulates prepared by spray drying had a maximum size of 15 µm, while the smallest size of 1.82 µm. Jeyakumari et al [14] and Kolanowski et al [8] observed spherical structure of microencapsulates with different sizes by spray drying of oil. Surface morphology of both CGM and CGME fish oil encapsulates showed individual spherical shape (Figure 1(b, c)).…”
Section: Hygroscopicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The study, as stated by Chávez‐Mendoza et al () presented that the frozen storage had an adverse effect on meat quality of rainbow trout due to the reduction of PUFA up to 32.55%. Also, as an alternative way to directly protect fish oil, fish gelatin, and maltodextrin as microcapsulated wall materials indicated a protective effect on PUFA content from oxidation in the fish oil encapsulates as compared to the control group samples (Annamalai, Dushyant, & Gudıpati, ). As can be seen from different studies, PUFAs could be easily reacted with oxygen due to their high degree of unsaturation during storage period.…”
Section: Resultsmentioning
confidence: 99%